ALGORITHM FOR ASSESSING THE STABILITY OF A DIGITAL SYSTEM BASED ON THE CONDITION OF APPROACHING HIDDEN OSCILLATIONS (Scientific journal of the Fergana State University, 2024)
The article discusses the issue of simplifying the mechanism for establishing stability conditions in a structurally uncertain numerical control system determined on the basis of discrete input-output data. At the center of the problem was the construction of a mathematical description expressing the general relationship between system stability and latent oscillations. At the same time, the feasibility of developing a system model and analytical form of problems is based on the method of experimental statistical modeling that explains empirical dependencies. As an information method for describing the object of the problem, a structural study of the object and a synthesis of characteristics in various dimensions of the system were used. It has been proven that the conditions for assessing hidden patterns in the system are not impossible in the presence of discrete input-output data. From a practical point of view, the possibility of developing a mathematical description that reveals the nature of hidden vibration and allows it to be expressed numerically for each discretely defined system has been proven. It has been confirmed that the stability of a structurally uncertain system can be controlled by only two states of oscillation. The condition for stabilization of a digital system is that the dynamic interval of actual fading before the change in latent vibrations exceeds the interval obtained as a result of the response function.